Impulsivity is Associated with Early Sensory Inhibition in Neurophysiological Processing of Affective Sounds - Soshi, Takahiro; Noda, Takamasa; Ando, Kumiko; Nakazawa, Kanako; Tsumura, Hideki; Okada, Takayuki (Frontiers in Psychiatry, 2015)
Impulsivity is widely related to socially problematic behaviors and psychiatric illness. Previous studies have investigated the relationship between response inhibition and impulsivity. However, no study has intensively examined how impulsivity correlates with automatic sensory processing before the drive for response inhibition to sensory inputs. Sensory gating is an automatic inhibitory function that attenuates the neural response to redundant sensory information and protects higher cognitive functions from the burst of information processing. Although sensory gating functions abnormally in several clinical populations, there is very little evidence supporting sensory gating changes in conjunction with impulsivity traits in non-clinical populations. The present study recruited healthy adults (n = 23) to conduct a neurophysiological experiment using a paired click paradigm and self-report scales assessing impulsive behavioral traits. Auditory stimuli included not only a pure tone, but also white noise, to explore the differences in auditory evoked potential responses between the two stimuli. White noise is more affective than pure tones; therefore, we predicted that the sensory gating of auditory evoked potentials (P50, N100, P200) for white noise would correlate more with self-reported impulsivity than with those for pure tones. Our main findings showed that sensory gating of the P50 and P200 amplitudes significantly correlated with self-reported reward responsiveness and fun-seeking, respectively, only for white noise stimuli, demonstrating that higher-scoring impulsivity subcomponents were related to greater sensory gating. Frequency-domain analyses also revealed that greater desynchronization of the beta band for the second white noise stimulus was associated with higher motor impulsivity scores, suggesting that an impulsivity-related change of sensory gating was associated with attentional modulation. These findings indicate that the measurement of sensory gating of white noise may be an efficient tool to evaluate impulsivity in non-clinical populations, and should also be applied to clinical populations.